The Role of New Media in Building Virtual Community Type Unite - Setiawan, Kurnia; Widitiarsa, Arsa; Razali, Geofakta; Putranto, Algooth (Jurnal Komunikasi, 2024)
New media which is currently developing in line with developments in information technology brings a new dimension to the field of communication. Physical public space is shifting and find a new platform, namely digital public space which brings today's society to live in a connected world. One of the virtual communities on a global scale whose founder came from Indonesia is "Type Unite" Virtual community “Type United” built in 2017. It began from informal discussion about student collaboration project in Typography. The result of the project was uploaded in social media (facebook). The research question; how the role of new media in building virtual community “Type Unite”. Research approach used mediamorphosis analysis from Fiddler. Mediamorphosis describes the changes that occur in media production, distribution, and consumption. Technology product applications transcend the borders of traditional media and become an actor on a global scale. The new media applications, products such as information and news are rapidly spreading from the country of manufacture to the whole world. The internet has been improved in these developments and increased the relationship of many tools with each other. Social media also part of the new media like internet. Social media is not only as an information instrument but also unify some Typography lecturers from all over the world to join in virtual community. They made global alliance from all over countries. According to the principles of media morphosis analysis, there are co-evolution, convergency, and complexity in “Type Unite” as virtual community. Typographers from all over the world has adapted with new media platform and productively use as a tools to collaborate and to do some typography works. New media supports the participant to interact and build virtual community in global collaboration. Type Unite can be a model and inspiration for others to make a virtual community with specific theme.